FUNGITOXICITY OF ESSENTIAL OILS ON Plasmopara viticola, CAUSAL AGENT OF GRAPEVINE DOWNY MILDEW - Fialho, Regis De Oliveira [UNESP] (2017)
This study aimed to evaluate the fungitoxic (antifungal) effect of seven essential oils on Plasmopara viticola, the causal agent of grapevine downy mildew. The cinnamon, eucalyptus globulus, marjoram, melaleuca, peppermint, oregano and white thyme essential oils were compared with the mancozeb + metalaxyl-M fungicide. Three experiments were conducted to evaluate the effect of essential oils on spore germination. The first experiment evaluated the effect of direct contact of essential oils on the pathogen; the second evaluated the effect of volatile compounds on the pathogen and the third assessed the behavior of essential oils, when applied to vine leaves in field conditions, on the pathogen. All essential oils inhibited the spores' germination, but in varying degrees, in addition, presenting fungistatic activity. All the essential oils showed chemical instability when the incubation time or the interval between products application where increased, all oils decrease antifungal activity percentage. Noteworthy, the cinnamon and the eucalyptus globulus essential oils were the most fungitoxic (antifungal) on P. viticola.